When history and memory collide : contextualising gendered representations of the partition of India in women's writings - Lim, Denise Zhi Qing (2017)
2017 marks the 70th anniversary of the Partition of India. 70 years on, “Partition” has become byword for widespread communal violence in India. This is especially pertinent, as Hindu nationalism is on the rise with the prominence of the ruling Bharatiya Janata Party (BJP), increasing frequency of communal violence, and the passing of the last Partition survivors. Yet, there is no official acknowledgement of the enormous scale of violence that happened during Partition, and official narratives neglect women’s experiences of violence during Partition.